The Oil Major Approval of tanker vessels and its’ effects on charter-parties in relation to claims against ship-owners - Valpīters, Roberts (Riga Graduate School of Law, 2018)
The Oil Major approval of tanker vessels is an essential part of the daily commercial transactions that are conducted by oil tankers across the globe. Without the Oil Major approval, it is highly difficult for the vessels to profitably trade oil, and in cases the approval is lost, it may cause issues of liability from the ship-owners part, towards the charterers subject to charter-party. The Oil Majors and other lesser oil companies have established a unified system that allows them to regulate the quality of the vessels and oil that is being traded in the international markets, in order to ensure uniform standards and quality among all merchants. The thesis aims to analyze the approval of tanker vessels by the Oil Majors, and the related process and formalities, according to the available case law.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Maritime law; Environmental law